The Challenges of Implementing Digital Literacy in Teaching and Learning Activities for EFL Learners in Indonesia - Devi Purmayanti (Celebes Scholar pg, 2022)
The proper comprehension and use for digital technology of English teachers can drive the learning process to ideal learning activities. Vise-versa improper comprehension of digital literacy by the teachers unexpectedly gives issues to learning process. Teachers must comprehend well the power of digital technology from aspects, such as: challenges, strategies, and the ideal purpose of digital literacy to be embeded in English language teaching. This critical review reveals the challenges of the implementation of digital literacy to support English language teaching. There are three main challenges that the students face in implementing digital literacy in the classroom. Those are lack of supportive access and digital tools, lack of digital literacy skill from teachers and also students’ lack of digital literacy skills. However, by acknowledging those issues, it could raise the attention of learners, teachers, and policymakers leading them to take further actions to mitigate the barriers.